Isu-isu investasi dalam industri takaful: belajar dari pengalaman Malaysia - Abdullah, Nurdianawati Irwani; Laldin, Mohd Akram; Ahmad, Muhammad Ali Jinnah; Abdullah, Syahida; Md. Zuki, Mazrul Shahir; Ali, Mohammad Mahbubi (2012)
This paper is a review of takaful industry based on Malaysian experience